Alcohol use disorders in Europe: A comparison of general population and primary health care prevalence rates. (2nd September 2016) - Manthey, Jakob; Gual, Antoni; Jakubczyk, Andrzej; Pieper, Lars; Probst, Charlotte; Struzzo, Pierluigi; Trapencieris, Marcis; Wojnar, Marcin; Rehm, Jürgen
Abstract: Aims . Alcohol use disorders (AUDs) are prevalent in Europe but occurrence in primary care and the proportion of treated cases are understudied. This study reports prevalence of AUDs and their treatment in European primary health care settings and compares them with general population estimates. Procedure . We sampled 358 general practitioners (GPs, refusal rate: 56.4%) across six European countries (Germany, Hungary, Italy, Latvia, Poland, and Spain) who assessed 13, 003 patients including providing AUD diagnoses. A subsample of 8, 476 patients (refusal rate: 17.8%) was interviewed subsequently, assessing DSM-IV AUD diagnoses via the Composite International Diagnostic Interview. Final AUD diagnoses combined GP and patient interview information. Findings . Past year AUDs were prevalent with 11.8% (95% CI: 11.2–12.5%) across all regions, which is 1.6 times the European general population AUD estimate. Of those diagnosed with AUDs, 17.7% (95% CI: 15.4–20.0%) received professional help. Compared to general population estimates, AUDs and their treatment were more prevalent in primary care settings in most countries, with disproportionally high AUD rates in Italy and Spain and unexpectedly low AUD rates in Hungary. Conclusions . We found higher prevalence and treatment rates of AUDs in primary health care compared to general population surveys, with large variability between the observed countries.